Arctigenin improves vascular tone and decreases inflammation in human saphenous vein - Daci, A.; Neziri, B.; Krasniqi, S.; Cavolli, R.; Alaj, R.; Norata, Giuseppe; Beretta, G. (Elsevier Science, 2017)
© 2017 Elsevier B.V. The goal of this study was to test the effects of bioactive phenylpropanoid dibenzylbutyrolactone lignan arctigenin (ATG) in vascular tone. Human bypass graft vessel, from a saphenous vein (SV), were set up in organ bath system and contracted with potassium chloride (KCl, 40 mM). Two concentration–response curves of noradrenaline (NE) (10 nM–100 µM) separated with an incubation period of 30 min without (Control) or with ATG (3–100 µM) were established. Inhibitors of nitric oxide, prostaglandins, K + related channels or calcium influx were used to delineate the molecular mechanisms beyond ATG effects. To investigate anti-inflammatory actions, SV were treated with 10 µM or 100 µM ATG and incubated for 18 h in the absence or presence of both interleukin-1beta (IL-1ß) and lipopolysaccharide (LPS) to mimic the physiological or inflamed tissue conditions. Proatherogenic and inflammatory mediators Interleukine-1 beta (IL-1ß), Monocyte Chemoattractant Proteine-1 (MCP-1), Tumor Necrosis Factor- a (TNF-a), Interleukine-6 (IL-6), Prostaglandin E 2 (PGE 2 ) and Interleukine-8 (IL-8) in the supernatant were measured. ATG significantly decreased vascular contractile response to NE. Moreover, it reduced contractions induced by KCl and cumulative addition of CaCl 2. The mediators were significantly increased in inflammatory conditions compared to normal conditions, an effect which was inhibited by ATG (10 and 100 µM). ATG reduces contractions in SV and decreases the production of proinflammatory-proatherogenic mediators, setting the stage for further evaluating the effect of ATG in cardiovascular diseases.